KONSEP IQRA’ PADA ANAK USIA DINI - Hikmaturrahmah, Hikmaturrahmah (Musawa: Journal for Gender Studies, 2020)
The command to iqra in Qur'an as the first revelation is a concept of command to read. In this context, the word iqra (read) means an activity to get to know, comprehend, analyze, observe, and learn all things in life. It could also be specifically interpreted as reading books. The book here is not limited to Qur'an, but each and every beneficial thing. Children are blank slates of human that must be introduced to books and reading. However, it is obvious that there is a difference in teaching reading to early childhood and to adults. Reading is an enjoyment for children, full of pictures and colors, laughter and happiness. The essence of children is to be engaged in new things. So, reading is a way to introduce numerous new things to early childhood.